Fertiliser drawn forward osmosis for wastewater recycling - Tan, Chen Yee (Nanyang Technological University, 2024)
Water security remains an everlasting problem to developed and developing countries alike and has undoubtedly garnered significant attention with regards to obtaining sources of water. Forward Osmosis (FO) is a promising, emerging technology that could potentially alleviate much of the increasing pressure on water supply. The application of FO has since expanded tremendously for the betterment of water quality and supply such as in the field of Fertilizer-Drawn Forward Osmosis (FDFO). In this study, we examined FDFO using hydroponics wastewater as feed solution (FS) against a commercially available nutrient solution catered for hydroponics as the draw solution (DS) across an asymmetric membrane. A lab-scale experiment setup was established to investigate the effects of different volumes on water flux, recovery rate, and reverse salt flux (RSF). A series of experiments were then performed to compare the differences in said parameters across the experiments without recovery of the DS to simulate actual application of direct fertigation for hydroponics growth. The contents of the DS and FS were then analysed to determine the transport direction and extent of the solutes across the membrane.